فناء النار وخلف الوعيد بين الرحمة وإغراء العبيد - Mohammad Amin Ali Eyssa; Ahmad Najaa' Mokhtar (Sultan Sharif Ali Islamic University (UNISSA), Brunei Darussalam, 2026)
Tier 4- Non-Indexed Publication